The role of livestock in integrated nutrient management in semi-arid West Africa - Williams, Timothy O.; Hiernaux, Pierre H.Y.; Fernández Rivera, S. (Reading University, 1997)
This paper outlines the role of livestock in integrated nutrient management in semi-arid west Africa. Farmers' strategies in the use of animal manure as well as research efforts to better understand the process of nutrient cycling through livestock in mixed farming systems are described. It concludes by suggesting ways in which research, government policies and farmers' practices could be coordinated to ensure sustainable nutrient management and agricultural Development.